2010
DOI: 10.3155/1047-3289.60.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Traffic Emissions on the Carcinogenic Polycyclic Aromatic Hydrocarbons in Outdoor Breathable Particles

Abstract: Because polycyclic aromatic hydrocarbons (PAHs) have been proven to be toxic, mutagenic, and/or carcinogenic, there is widespread interest in analyzing and evaluating exposure to PAHs in atmospheric environments influenced by different emission sources. Because traffic emissions are one of the biggest sources of fine particles, more information on carcinogenic PAHs associated with fine particles needs to be provided. Aiming to further understand the impact of traffic particulate matter (PM) on human health, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 36 publications
5
15
0
4
Order By: Relevance
“…All these places have the characteristic of being large urban areas with high vehicular activity. However, the average total concentration was higher than that reported in Atlanta, USA (1.52 ng·m −3 , Σ15 PAHs) [16], Wanqingsha, Hong Kong (19.3 ng·m −3 , Σ17 PAHs) [17] Porto, Portugal (13.3 ng·m −3 , Σ15 PAHs) [18] and Mount Taishan, China (7.05 ng·m −3 Σ15 PAHs) [19]. These results are consistent with the type of industrial and/or vehicular activities, which occur in this urban area.…”
Section: Comparison With Other Studiesmentioning
confidence: 59%
“…All these places have the characteristic of being large urban areas with high vehicular activity. However, the average total concentration was higher than that reported in Atlanta, USA (1.52 ng·m −3 , Σ15 PAHs) [16], Wanqingsha, Hong Kong (19.3 ng·m −3 , Σ17 PAHs) [17] Porto, Portugal (13.3 ng·m −3 , Σ15 PAHs) [18] and Mount Taishan, China (7.05 ng·m −3 Σ15 PAHs) [19]. These results are consistent with the type of industrial and/or vehicular activities, which occur in this urban area.…”
Section: Comparison With Other Studiesmentioning
confidence: 59%
“…As the same with the study of Kim et al (2013), the study shows that the acenaphthene marks the highest concentration among gaseous and particle PAHs. It is reported that the particle PAHs are detected from materials with 5-7 rings (Slezakova et al, 2010;Lizhong Zhu, 2009;Li et al, 2006) and the heavy-weight PAHs are mainly related to the particle materials (Pan et al, 2012). The study shows that the concentration distribution of the particle materials with more than 5 rings increases compared to the gaseous ones and the acenaphthene with 3 rings shows the highest concentration from all the facilities.…”
Section: Distribution Of Pah Compounds In Gaseous and Particulate Pmentioning
confidence: 76%
“…The PAHs with 2-3 rings are detected in the gaseous phase much and known that they mark relatively high concentrations and their emission sources are placed indoor (Castro et al, 2011;Slezakova et al, 2010;Lizhong Zhu, 2009;Fanf et al, 2004). The study also shows that the acenaphthene, phenanthrene, naphthalene and fluorene, PAHs with 2-3 benzene rings, mark high concentrations.…”
Section: Distribution Of Pah Compounds In Gaseous and Particulate Pmentioning
confidence: 99%
“…PAHs with low molecular weight are usually found more in the vapor phase, but the majority of compounds with four or more rings are mainly particulate-bound Srogi, 2007). The series of related studies performed in Oporto, Portugal Slezakova et al, 2010 showed that in urban environments with major influences of vehicular traffic emissions, on average 5 to 8% of total particulate PAH content was associated with bigger particles (i.e. PM 2.5-10 ) whereas 92-95% of total PAH content was present in PM 2.5 ; in a remote site 95 % of PAHs were PM 2.5 -bound .…”
Section: Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%